School-Based Management for Education Quality: Evidence from Procurement of Facility and Infrastructure - Kumba Digdowiseiso (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to examine the implementation of school-based management in the acquisition of facilities and infrastructure targeted at enhancing educational quality. This study employs a qualitative research method as the design. This study took place at a senior high school in East Jakarta as the research setting. Data were collected from observation and Focused Group Discussion (FGD). Furthermore, the obtained data were analysed using Miles Huberman qualitative analysis procedures. The reported result has been quite successful. It is shown by the performance is carried out in the procurement of school facilities and infrastructure which is applied in the school budget planning stage, school financial accounting, and implements accountability school finances. This application will lead to public trust in schools so that education based on mutual trust will improve the quality of education.